RELEVANSI EPISTEMOLOGI KARL R. POPPER DALAM PEMIKIRAN ISLAM - Rahman, Saifur (KOMUNIKE, 2017)
A thought is not born from a vacuum, so that every thought has its own unique and different from each other, before and after. Knowledge and experience of someone greatly influence the pattern she thought. No exception was a great thinker origin Austria and influence on the modern century and even till now he is Karl R. Popper. The concept of epistemology Popper is relating to falsification human knowledge to answer the question of demarcation by the Wina Circle. Their demarcation is deemed irrelevant to the science that became the border wall between meaningful and meaningless. This is caused by the principle of verification method using induction. Where induction seen redundant and inconsistent. As for the relevance of epistemology Popper with the thought of Islam can foster an attitude of tolerance of logical thinking. The critical attitude of the very means to resolve the tension between the two thoughts are not the same. Critical are not only aimed at the external but more internal. So one another will open up to dialogue are thought-provoking.